PENGARUH PROJECT BASED LEARNING (PjBL) BERBANTUAN E-LEARNING TERHADAP HASIL BELAJAR MAHASISWA - Arif Rahman Hakim; Hairunisa Hairunisa; Abd. Haris Abd. Haris (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Bima, 2021)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model assisted by e-learning on the learning outcomes of PGSD students. This type of research is a quasi-experimental research design with posttest only control group design. The sample in this study is the second semester PGSD students, totaling 40 people with random sampling technique. Data collection techniques were carried out by interviews, tests and questionnaires. Data analysis in this study used t-test. Based on the results of the posttest that has been carried out, the average value of the experimental class is 74.5 and the control class is 60.5. Meanwhile, based on the results of hypothesis testing with t-test, the t-count value is 2.358 while the t-table is 2.045 at a significant level of 5% with the test criteria Ho accepted where t-count = 2.358 > t-table = 2.045. This means that there is a significant effect on the implementation of PjBL assisted by e-learning on learning outcomes with a correlation coefficient of 0.435 (enough category). This shows that the application of the Project Based Learning (PjBL) learning model assisted by e-learning has a positive influence on student learning outcomes.